2020
DOI: 10.1098/rsif.2020.0344
|View full text |Cite
|
Sign up to set email alerts
|

Mobile device location data reveal human mobility response to state-level stay-at-home orders during the COVID-19 pandemic in the USA

Abstract: One approach to delaying the spread of the novel coronavirus (COVID-19) is to reduce human travel by imposing travel restriction policies. Understanding the actual human mobility response to such policies remains a challenge owing to the lack of an observed and large-scale dataset describing human mobility during the pandemic. This study uses an integrated dataset, consisting of anonymized and privacy-protected location data from over 150 million monthly active samples in the USA, COVID-19 case data and census… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 19 publications
2
53
0
Order By: Relevance
“…With the availability of recent data, there is an emerging number of studies with more extended periods. Xiong et al (2020a) analyzed the inflow mobility in US counties from March 1 to June 9. He found a positive relationship between the COVID cases and inflow in counties.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the availability of recent data, there is an emerging number of studies with more extended periods. Xiong et al (2020a) analyzed the inflow mobility in US counties from March 1 to June 9. He found a positive relationship between the COVID cases and inflow in counties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, in modeling practice, accounting for spatial autocorrelation is less commonly seen in contemporary works. Xiong et al (2020a) also recommended addressing this issue in future studies. The second issue is about the data.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the proposed framework can also be applied to other realms, such as business development and public health. For instance, during the COVID-19 pandemic, a handful of research utilized the MDLDs to derive the travel statistics, i.e., trip rate and inflow, and study their correlation with the new COVID-19 infections (Xiong et al 2020a , b ; Pan et al 2020 ). By applying our proposed framework to the MDLDs, the correlation between multimodal travel and the spread of COVID-19 can be studied to support governments decision makings on transit or airline operations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Lots of applications have been developed using the LBS data. For instance, a recent smartphone-enhanced travel survey conducted in the U.S. used a mobile application, rMove developed by Resource Systems Group (RSG), to collect high-frequency location data and let respondents recall their trips by showing the trajectories in rMove (RSG 2014 , 2015a , b , 2017 ); Airsage leveraged LBS data to develop a traffic platform that can estimate traffic flow, speed, congestion and road user sociodemographic for every road and time of day (AirSage 2020 ); Maryland Transportation Institute (MTI) at the University of Maryland (UMD) developed the COVID-19 Impact Analysis Platform ( data.covid.umd.edu ) to provide insight on COVID-19’s impact on mobility, health, economy and society across the U.S. (Zhang et al 2020 ; Xiong et al 2020a , b ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our work contributes to a growing body of research analyzing the impact of government policies on factors such as mobility. 12,13 Prior research has found that government policies as well as pandemic severity impacts social distancing that is practiced within communities, and that less social distancing is practiced after observing local mitigation. 8 Researchers have also shown that social distancing and lower population density may be associated with decreased spread of the coronavirus.…”
Section: Introductionmentioning
confidence: 99%